Prolonged prostaglandin E1 therapy in a neonate with pulmonary atresia and ventricular septal defect and the development of antral foveolar hyperplasia and hypertrophic pyloric stenosis. (May 2013) - Perme, Tina; Mali, Senja; Vidmar, Ivan; Gvardijančič, Diana; Blumauer, Robert; Mishaly, David; Grabnar, Iztok; Nemec, Gregor; Grosek, Stefan
Abstract Prostaglandin E1 (alprostadil) is widely used for maintaining the patency of ductus arteriosus in ductus-dependent congenital heart defects in neonates to improve oxygenation. Among more common side effects are fever, rash, apnoea, diarrhoea, jitteriness, and flushing. More severe side effects are brown fat necrosis, cortical hyperostosis, and gastric outlet obstruction, most commonly the result of antral foveolar hyperplasia or hypertrophic pyloric stenosis. We report on an infant with a ductus-dependent congenital heart defect who developed symptoms and sonographic evidence of focal foveolar hyperplasia and hypertrophic pyloric stenosis after prolonged treatment with prostaglandin E1. Gastrointestinal symptoms persisted after corrective cardiac surgery, and pyloromyotomy was required. Study of the case and of available literature showed an association between the total dose of prostaglandin E1 administered and duration of treatment and the development of gastric outlet obstruction. We conclude that if patients are treated with a prostaglandin E1 infusion, careful monitoring for symptoms and signs of gastric outlet obstruction is required.